Basic Statistics Relating to the Indian Economy 1950-51 to 1955-56 - Planning Commission (Planning Commission, 1957)
The document "Basic Statistics Relating to the Indian Economy (1950-1956)" provides a detailed overview of India’s economic, industrial, social, and educational indicators during the early post-independence period and the initial phase of the First Five-Year Plan. Key findings include steady growth in national income and per capita income, significant gains in agricultural production and irrigation, rising industrial output, and expanding electricity generation. Wholesale price indices fell, indicating improved price stability, while employment in central government positions increased. The report also highlights growth in selected industries such as metals, cement, and chemicals, alongside improvements in infrastructure, transport, and foreign trade management. Furthermore, cooperative societies witnessed asset, deposit, and loan growth, while education expanded through higher enrollment, increased teacher numbers, and growth in higher and technical education. Overall, the data reflects a period of economic consolidation, industrialization, and social development, providing essential insights for policy formulation and planning in India’s formative economic years.
Statistics & Surveys Division Planning Commission New Delhi
Statistics & Surveys Division Planning Commission New Delhi
Keywords: Indian Economy; Basic Statistics; Planning Commission India; First Five Year Plan; National Income; Per Capita Income; Agriculture; Industrial Production; Electricity Generation; Foreign Trade; Price Indices; Employment Trends; Cooperative Societies